Management of Different Types of Pneumothorax at Dhulikhel Hospital, Kathmandu University Hospital - Shrestha, B.; Karmacharya, R. M.; Pant, S. (Kathmandu University Medical Journal, 2020)
Background Pneumothorax is defined as the presence of air in the pleural cavity. Pneumothorax can be classified as Spontaneous and Traumatic according to the etiology. Spontaneous pneumothorax is further classified as Primary and Secondary. Objective This study was conducted to know the management of different types of pneumothorax at Dhulikhel Hospital, Kathmandu University Hospital. Method This was a hospital based retrospective study conducted at Dhulikhel Hospital, Kathmandu University Hospital. Patients admitted in Surgery Ward with diagnosis of Pneumothorax from January 2018 to December 2019 were included in this study. Result This study included 144 patients with pneumothorax age ranging from 14 years to 94 years. Most of the patients were male with male:female ratio of 3.8:1. Eighty-four (58.03%) patients had Traumatic pneumothorax followed by Secondary spontaneous pneumothorax in 53(36.08%) patients and Primary spontaneous pneumothorax in seven (4.86%) patients. Among 144 patients, chest tube drain was required in 135 patients and nine patients were managed conservatively. One patient underwent Video Assisted Thoracoscopic Surgery (VATS) with Bullectomy and mechanical pleurodesis. Sixteen patients had persistent pneumothorax, among which six patients required chemical pleurodesis, two patients required negative suction therapy and five patients required both chemical pleurodesis and negative suction therapy. Conclusion This study showed pneumothorax to be more common in male population. Traumatic pneumothorax was the most common type followed by Secondary spontaneous pneumothorax and Primary spontaneous pneumothorax.